Brain contains two forms of synaptic vesicle protein 2. - Bajjalieh, S M (1993)
Molecular cloning of a cDNA encoding synaptic vesicle protein 2 (SV2) revealed that it is homologous to a family of proton cotransporters from bacteria and fungi and to a related family of glucose transporters found in mammals. The similarity to proton cotransporters raised the possibility that SV2 might mediate the uptake of neurotransmitters into vesicles, an activity known to require a proton gradient. To determine whether SV2 is a member of a family of vesicular proteins, we used the SV2 clone to screen for similar cDNAs in rat brain. We characterized 42 clones, 25 of which encode SV2 and 4 of which encode a protein, SV2B, that is 65% identical and 78% similar to SV2. The protein encoded by SV2B cDNA is recognized by the monoclonal antibody that defines the SV2 protein. When SV2B is expressed in COS cells, antibody labeling is reticular in nature, suggesting that SV2B, like SV2 (hence, SV2A), is segregated to intracellular membranes. The expression of SV2B is limited to neural tissue. While both forms of SV2 are expressed in all brain regions, SV2B is expressed at highest levels in the cortex and hippocampus, whereas the highest level of expression of SV2A is in subcortical regions. Therefore, the SV2 proteins, like other characterized synaptic vesicle proteins, comprise a small gene family.